The Modulation of Apoptotic Pathways by Gammaherpesviruses - Banerjee, Shuvomoy; Uppal, Timsy; Strahan, Roxanne; Dabral, Prerna; Verma, Subhash C. (Frontiers in Microbiology, 2016)
Apoptosis or programmed cell death is a tightly regulated process fundamental for cellular development and elimination of damaged or infected cells during the maintenance of cellular homeostasis. It is also an important cellular defense mechanism against viral invasion. In many instances, abnormal regulation of apoptosis has been associated with a number of diseases, including cancer development. Following infection of host cells, persistent and oncogenic viruses such as the members of the Gammaherpesvirus family employ a number of different mechanisms to avoid the host cell’s “burglar” alarm and to alter the extrinsic and intrinsic apoptotic pathways by either deregulating the expressions of cellular signaling genes or by encoding the viral homologues of cellular genes. In this review, we summarize the recent findings on how gammaherpesviruses inhibit cellular apoptosis via virus-encoded proteins by mediating modification of numerous signal transduction pathways. We also list the key viral anti-apoptotic proteins that could be exploited as effective targets for novel antiviral therapies in order to stimulate apoptosis in different types of cancer cells.